2023
DOI: 10.1039/d3cp00475a
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the role of excess hydroxide ions in silicate condensation reactions

Abstract: Understanding the formation of silicate oligomers in the early stages of zeolite synthesis is critical. The pH and the hydroxyl ion are important in regulating the reaction rate and the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…In contrast to extensive research on the effect of cations on silicate reactions, the role of anions in this process has received relatively little attention. Recent work by Do et al 31 has demonstrated that OH – ion play a critical role in silicate condensation reactions by directly participating in these reactions. Chloride ion is another ubiquitous and crucial ion in various chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to extensive research on the effect of cations on silicate reactions, the role of anions in this process has received relatively little attention. Recent work by Do et al 31 has demonstrated that OH – ion play a critical role in silicate condensation reactions by directly participating in these reactions. Chloride ion is another ubiquitous and crucial ion in various chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These values are similar to the activation barrier of trimer ring condensation and Si–OH rupture, which are reported to be14.58 kcal mol −1 and 15.30 kcal mol −1 in the presence of ethylamine 24 but lower than those reported in other investigations performed in presence of anions such as 17.21 kcal mol −1 and 23.42 kcal mol −1 in the presence of Cl − ions 26 and 19.36 kcal mol −1 and 21.99 kcal mol −1 in the presence of OH − ions. 25 Fig. 13 suggests that the energy levels of the final product from two pathways are quite close to each other.…”
Section: Resultsmentioning
confidence: 80%
“…These values are lower than the activation barriers of dimer condensation and Si–OH rupture reported in previous literature, which are 13.86 kcal mol −1 and 15.06 kcal mol −1 in the presence of ethylamine, 24 14.82 kcal mol −1 and 19.36 kcal mol −1 in the presence of Cl − ions, 26 and 16.97 kcal mol −1 and 19.84 kcal mol −1 in the presence of OH − ions. 25 It has already been established that the arrangements of hydroxyl groups in anionic-I intermediates make only M1 pseudorotation feasible and restrict M3 alt through steric hindrance or intramolecular H-bonds. It is evident from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations